Youth Economic Development Through the Production of Screen Printing at Karang Taruna, Medan Johor Sub-district - Berlianti; Sinaga, Randa Putra Kasea (Talenta Publisher, 2023)
Karang Taruna, Medan Johor sub-district is one of the youth groups that are active in organizing social activities to build the community. This they do so that youth as a support for the future can understand its role and function as part of a community group so as to avoid deviant behavior such as narcotics abuse. Narcotics abuse is a common problem in community groups, so when there is a youth group that has the goal of embracing youth for social activities is something that should be supported. One of the things that Karang Taruna, Medan Johor district has not done is the economic empowerment of youth in the form of sustainable efforts. This devotion seeks to facilitate youth by providing training such as clothing screen-printing production training, business management and product marketing so that they can have economic activities, both individually and in groups. The results of the training showed a significant increase in skills and an increasing interest in youth to open up screen printing entrepreneurial opportunities as an effort to form economic independence for Karang Taruna, Medan Johor Sub-district. This community service is an effort and the real role of the university of North Sumatra to provide benefits for the community.